The role of imaging in surgical planning for liver resection: what the radiologist need to know - Agostini, Andrea; Borgheresi, Alessandra; Floridi, Chiara; Carotti, Marina; Grazzini, Giulia; Pagnini, Francesco; Guerrini, Susanna; Palumbo, Pierpaolo; Pradella, Silvia; Carrafiello, Gianpaolo; Vivarelli, Marco; Giovagnoni, Andrea (Acta Biomedica Atenei Parmensis, 2020)
The management of patients undergoing surgical resection for liver malignancies requires a multidisciplinary team, including a dedicated radiologist. In the preoperative workup, the radiologist has to provide precise, relevant information to the surgeon. This requires the radiologist to know the basics of surgical techniques as well as liver surgical anatomy in order to help to avoid unexpected surgical scenarios and complications. Moreover, virtual resections and volumetries on radiological images will be discussed, and basic concepts of postoperative liver failure, regeneration, and methods for hypertrophy induction will be provided.